LEGAL PROTECTION OF CHILDREN AS CONVICTS - Hasibuan, Hamdi (Proceeding International Seminar of Islamic Studies, 2023)
Appropriate handling and law enforcement is needed against children as perpetrators of criminal acts of abuse. If a child violates the law, the child must be held accountable for his actions, however, even though he must be held accountable for his actions, the child must be protected. Child protection is closely related to the five pillars namely, parents, family, community, government, regional government and the state. The five are related to each other as child protection providers. According to Article 4 of the SPPA Law, a child who is undergoing a criminal period has the right to Remission or reduction of his criminal past, Assimilation, Leave to visit family, Conditional release, Leave before release, Conditional leave and other rights in accordance with statutory regulations. In addition, the principle of protection in the SPPA Law can be seen in terms of imposing sanctions. Children as perpetrators of criminal acts can be subject to 2 (two) types of sanctions, namely action sanctions (perpetrators of crimes under 14 years old) and criminal sanctions (Article 69 of the SPPA Law).